La objetividad de las creencias, el desacuerdo razonable y la deliberación política (2011)
This paper is part of a broader argument that seeks to offer a justificationfor political (and law’s) authority. The aims here are twofold: to investigatethe role of truth in political argument and to place the problem of reasonabledisagreement. More precisely, the argument focuses on the possibilityof political deliberation. Political deliberation figures as a preliminary stageof political decisionmaking. It has to do with a confrontation betweenvarious incompatible substantive beliefs which, in despite of this, seem tobe all reasonable. How can citizens holding incompatible beliefs engage ina common enterprise of justifying them to one another? That is the mainquestion.